Evaluation of Companies: Theories, Process and Methods - Gaytán Cortés, Juan (Mercados y Negocios, 2025)
Business evaluation is the systematic process of analyzing and assessing the performance of an entity, whether it is a company, organization, or project, about specific previously established objectives. This analysis can be performed at any stage of the business life cycle and covers financial, operational, and strategic aspects.